2006
DOI: 10.1002/ps.1319
|View full text |Cite
|
Sign up to set email alerts
|

Lack of cross‐resistance to Mtx1 from Bacillus sphaericus in B. sphaericus‐resistant Culex quinquefasciatus (Diptera: Culicidae)

Abstract: The toxicities of Mtx1 toxin against dipteran and lepidopteran species have been evaluated in this study. It was shown that Mtx1 has little or no toxicity to the tested lepidopteran species, but has moderate-level toxicity to Aedes albopictus Skuse (Diptera: Culicidae) and high-level toxicity to both susceptible and binary toxin-resistant Culex quinquefasciatus Say (Diptera: Culicidae). The LC(50) values of Mtx1 against a susceptible C. quinquefasciatus colony SLCq and two resistant colonies RLCq1/C3-41 and RL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…quinquefasciatus , suggesting that Mtx1 has a different mode of action than Bin and lacks cross-resistance to B. sphaericus -resistant Cx. quinquefasciatus (Wei et al, 2007). …”
Section: Resistance and Receptorsmentioning
confidence: 99%
“…quinquefasciatus , suggesting that Mtx1 has a different mode of action than Bin and lacks cross-resistance to B. sphaericus -resistant Cx. quinquefasciatus (Wei et al, 2007). …”
Section: Resistance and Receptorsmentioning
confidence: 99%
“…israelensis Cry-toxins and toxin combinations, including Cry4Aa, Cry4Ba, Cry4Aa + Cry4Ba, Cry4Aa + CryBa + Cry11Aa, and Cry4Aa + CryBa + Cry11Aa + Cyt1Aa. The presence of cross-resistance in Cry-toxin selected C. quinquefasciatus is intriguing because of the absence of any such cross-resistance in L. sphaericus resistant mosquitoes (Wirth et al, 2007; Wei et al, 2007). In view of the significant cross-resistance shown among the various Cry toxins from B. thuringiensis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…in the B. sphaericus-resistant populations, their susceptibility to B. sphaericus C3-41 recovered, with the resistance ratio of fieldcollected larvae declining from 22,672-fold to 5.67-fold [41]; the gene exchange with populations in surrounding untreated areas may also have contributed to the rapid decline of resistance levels. There is a lack of cross-resistance between binary toxins and Mtx toxins [76], indicating that Mtx could be a potential tool to manage resistance to binary toxins in the future. It was suggested that once resistance to B. sphaericus is detected in the field, its use should be discontinued until the mosquito population becomes susceptible again because of the decline in number of resistant individuals [77].…”
Section: Resistance Managementmentioning
confidence: 99%